void changex(int kx,int l,int r)
{
changey(kx,1,1,h);
if(l==r) return;
int mid=l+r>>1;
if(x<=mid) changex(kx<<1,l,mid);
else changex(kx<<1|1,mid+1,r);
}
void changey(int kx,int ky,int l,int r) //方法一
{
sum[kx][ky]++;
if(l==r) return;
int mid=l+r>>1;
if(y<=mid) changey(kx,ky<<1,l,mid);
else changey(kx,ky<<1|1,mid+1,r);
}
void changey(int kx,int ky,int l,int r) //方法二
{
if(l==r)
{
sum[kx][ky]++;
return;
}
int mid=l+r>>1;
if(y<=mid) changey(kx,ky<<1,l,mid);
else changey(kx,ky<<1|1,mid+1,r);
sum[kx][ky]=sum[kx][ky<<1]+sum[kx][ky<<1|1];
}